Mechanism for soil reinforcement by electroosmosis incorporated with nanoclay. Issue 10 (27th July 2019) - Zhang, Heng; Hu, He; Lai, Yuanming; Niu, Fujun
Abstract: Although the effectiveness of electroosmosis and electrolyte injection on the dewatering of silt had been confirmed by previous studies, several issues remained with the two strengthening methods, which primarily limited their applications in practical engineering. In this context, a series of laboratory experiments were implemented in a customized apparatus to explore the simultaneous effect of electroosmosis and nanoclay on Wuhan lake silt. The results indicated that both electroosmosis and nanoclay had significant effect on improving the geotechnical properties of lake silt. And the addition of nanoclay further enhanced the electroosmotic reinforcement by increasing the cohesion and internal friction angle as much as 80.4% and 31.8% respectively, and by decreasing the plasticity index from 32.0 to 20.3. Furthermore, the micrographs of soil structure after treated with electroosmosis and various percentages of nanoclay agreed well with the experimental observations and suggested that the incorporation of electroosmosis and nanoclay can significantly promote the consolidation of lake silt.